MEDICINAL PLANTS WITH NEUROPHARMACOLOGICAL PROPERTIES FROM INDIAN ORIGIN - Jain, Sachin Kumar; Parihar, Sumit; Pandey, Neha (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Neuropharmacology is the scientific study of the effects of drugs on the central nervous system. Its primary focus is actions of medications for psychiatric and neurologic disorders as well as those of drugs of abuse. The goal of Neuropharmacology is to apply information about drugs and their mechanisms of action, develop safer and more effective treatments and eventually curative and preventive measures for a host of nervous system abnormalities. There are a number of drugs being used in the traditional medicine for treatment of various CNS disorders and presently many of these drugs are being explored scientifically to ascertain their CNS activities. Significant number of studies has been performed to find alternative treatment for diseases of the nervous forum by identifying structures with activity at the central nervous system. However, most of the screenings are usually conducted on an ad hoc basis and not systematically. The initial purpose of this review is to summarize plants with neuropharmacological activities, in particular, those that have not been fully studied and that have molecular mechanisms whose active constituents are responsible for the activities remained to be identified. The second purpose was to identify potential target plants for future studies of new and alternative therapies for the treatment of neurological disorders and neurodegenerative diseases.